1994
DOI: 10.1136/bjo.78.5.370
|View full text |Cite
|
Sign up to set email alerts
|

Expression of intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) on proliferating vascular endothelial cells in diabetic epiretinal membranes.

Abstract: The present study demonstrated the expression of intercellular adhesion molecule-i (ICAM-1) and vascular cell adhesion molecule-I (VCAM-1), the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 31 publications
2
25
1
1
Order By: Relevance
“…We believe that this finding cannot be attributed to the molecular size of VCAM-1, because serum diffusion is the primary reason for the intravitreous enhancement of a bigger molecule, such as IGF-I (19,20). Although our results do not suggest intraocular production of VCAM-1 in diabetic patients with PDR, there is relevant information arguing the contrary (7,8). To reconcile these opposing data, it is tempting to hypothesize that VCAM-1 is quenched by the retina in the passage from the blood stream to the vitreous fluid.…”
Section: Vcam-1 and Vegf In Diabetic Retinopathycontrasting
confidence: 53%
See 1 more Smart Citation
“…We believe that this finding cannot be attributed to the molecular size of VCAM-1, because serum diffusion is the primary reason for the intravitreous enhancement of a bigger molecule, such as IGF-I (19,20). Although our results do not suggest intraocular production of VCAM-1 in diabetic patients with PDR, there is relevant information arguing the contrary (7,8). To reconcile these opposing data, it is tempting to hypothesize that VCAM-1 is quenched by the retina in the passage from the blood stream to the vitreous fluid.…”
Section: Vcam-1 and Vegf In Diabetic Retinopathycontrasting
confidence: 53%
“…Interestingly, the expression of VCAM-1 has been found in epiretinal membranes from diabetic patients with PDR (7,8). In addition, it has been demonstrated that VCAM-1 promotes angiogenesis both in vitro and in vivo (9,10), but its relationship with VEGF has not been reported.…”
mentioning
confidence: 96%
“…Therefore, increased ICAM-1 levels have been suggested to play a crucial role in the development of DRP. VCAM-1 is also an adhesion molecule that mediates leukocyte adhesion and is considered to play an important role in the development of DRP (25). ET-1 has been demonstrated to play a role in the development of DRP in diabetic animals (13).…”
Section: Discussionmentioning
confidence: 99%
“…The test was performed according to the guidelines defined by Corretti et al (24) in a quiet room at a temperature of [22][23][24][25] in the morning (between 8:00-9:00 AM) after 12 hours of fasting. The use of alcohol, caffeine or vasoactive drugs and smoking were restricted during the fasting period.…”
Section: Evaluation Of the Endothelial Functionmentioning
confidence: 99%
“…VCAM-1, a member of the immunoglobulin supergene family of cellular adhesion molecules, is involved in the recruitment of leukocytes, their adhesion to vascular endothelium, and their subsequent migration into surrounding tissue. Interestingly, the expression of VCAM-1 has been found in epiretinal membranes from diabetic patients with PDR 109,110 . In addition, it has been demonstrated that VCAM-1 promotes angiogenesis both in vitro and in vivo 111 …”
Section: Vascular Cell Adhesion Molecule (Vcam)mentioning
confidence: 99%